2020
DOI: 10.21107/mediatrend.v15i2.8098
|View full text |Cite
|
Sign up to set email alerts
|

Kesesuain Karakteristik Pekerja dan Pekerja Pada Lingkungan Kerja Industri Mebel Ukir di Desa Petekeyan, Jepara-Jawa Tengah

Abstract: This study aims to describe the work environment in the furniture industry based on the suitability of the characteristics of workers and jobs. This study used descriptive qualitative method. The study was conducted on a case that occurred at the center of the carving furniture industry in Petekeyen, Jepara-Central Java. Data collection techniques are done by interview, observation and documentation. Then the data is analyzed inductively. The results showed that the working environment in the carved furniture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…A study conducted in Nepal with a noise frequency of up to 93.9 dB found that 44% of carpenters and 31% of carpenters met the NIHL criteria (Robinson et al, 2015). Abdul Malik 2020 stated that the characteristics of carved furniture workers in Petekeyan Jepara village were not using personal protective equipment when working, including ear protectors (Malik and Kristina, 2020). This is a risk of NIHL occurring in workers.…”
Section: Abstrakmentioning
confidence: 99%
“…A study conducted in Nepal with a noise frequency of up to 93.9 dB found that 44% of carpenters and 31% of carpenters met the NIHL criteria (Robinson et al, 2015). Abdul Malik 2020 stated that the characteristics of carved furniture workers in Petekeyan Jepara village were not using personal protective equipment when working, including ear protectors (Malik and Kristina, 2020). This is a risk of NIHL occurring in workers.…”
Section: Abstrakmentioning
confidence: 99%